Integer programming model for staff rostering problem: a case study on karaoke business in Seremban - Cheong, Lai Kean (2015)
In this study, an integer programming model is imposed on a karaoke service industry in Seremban. The model formulation is used to determine an optimal weekly shift schedule for the karaoke outlet's employees whom mainly consist of floor captain, service crew, receptionist cashier, chef and cleaner while satisfying several constraints. The integer programming model is implemented on Excel add-in solver routine and OpenSolver. The model enables the case study company's personnel management to develop a fair personnel schedule as needed and to effectively utilize personnel resources while satisfying several technical, legal and economic requirements. By using the OpenSolver, it enables to decrease the amount of time to create schedules from approximately 3 hours of manual work to less than 1 second. These encouraging achievements make the community optimistic about the advantages as other organizations can amass by introducing the operational research approaches in their management planning and decision making systems.